A Guide to Competitive Vouchers in Health - World Bank (Washington, DC, 2013)
This volume provides a broad outline of the problems health systems face, the rationale behind government intervention particularly in the form of subsidies, and the different ways that governments and donors subsidize health care. The guide provides readers with an understanding of the concept of competitive voucher schemes in health; the advantages competitive voucher schemes might offer as an instrument to delivery subsidies; circumstances where competitive voucher schemes are better suited than other instruments to deliver subsidies; and steps to follow when designing, implementing, monitoring and evaluating a competitive voucher scheme. Aimed at raising awareness among policymakers about voucher schemes, this book helps identify situations where vouchers may better achieve health objectives and provides guidance on the choices available and the decisions to be made. It highlights some of the pitfalls that voucher schemes have experienced to date, as well as the wide variation in format that a voucher scheme can take depending upon the health problems being addressed and the objectives that the policy-maker wishes to achieve.